M. Vaganay and the ‘Community Discourse’ - Butler, Basil Christopher 1902-1986 (1955)
M. Vaganay's important book, Le Problème Synoptique (Desclée, 1954), offers a ‘working hypothesis’ of some complexity. He suggests, among other things, that each of our Synoptic Gospels is dependent on a lost Greek translation (Mg) of a lost Aramaic Gospel; that Luke is also heavily, and Matthew slightly, indebted to Mark; and that Matthew and Luke further shared another lost source (Sg), to be distinguished from ‘Q’ inasmuch as several of the so-called Q passages are to be derived not from Sg but from Mg. In his long Excursus IV (pp. 361−404) M. Vaganay analyses the ‘discours communautaire’ of Matt. xviii. 1−35; Mark ix. 33−50; Luke ix. 46−50, and offers. a reconstruction of this discourse as, he thinks, it appeared in Mg.